Pemanfaatan Limbah Bulu Ayam Sebagai Bahan Tambahan Pakan Untuk Pertumbuhan (Berat dan Panjang) Ikan Nila (Oreochromis niloticus) - Pipit Ika Lestari; Yamtana Yamtana; Bambang Suwerda (Poltekkes Kemenkes Yogyakarta, 2016)
Chicken feather contain protein which is useful for the growth of livestock. The purpose of this study was to determine the effect of the addition of chicken feather waste to fish feed towards the growth (weight and length) of Nila fish. The chicken feather waste and feed preparation was took place at Sekawis Village of Kecamatan Kebonarum in Madiun. The breeding ponds of the fish was located at the Polytechnic of Health of Yogyakarta, in Tata Bumi Street No. 3 Banyura-den, Gamping, Sleman, Yogyakarta. The Nila fish was obtained from “Mina Kepis” fish breeder community in Burikan Sub Village, Sumberadi Village, Mlati Subdistrict, Sleman Regency. The research method used was true experiment with pre-test post-test control group design. As the independent variable was three addition variation of chicken feather waste, i.e. 4 %, 7 %, and 10 %. The number of Nila fish for each feed variation was 20. The measurement of post-test was after 30 days feeding. The results of One Way Anova test at 95 % significance level show that the growth differences among the three variation of feed were signicant (p-values < 0,001), and the subsequent LSD test concludes that the 10 % addition of chicken feather waste to fish feed is the most effective towards the growth of Nila fish.